The Influence of University X's Marketing Mix on Prospective Students' Purchase Intention in Bandung City - Samuel Tarigan; Cynthia Indira Pohe (Green Publisher Indonesia, 2026)
This study analyzes the effect of service marketing mix elements—product, price, place, promotion, people, process, and physical evidence—on the purchase intention of prospective students toward University X in Bandung. The research addresses increasing competition among private universities and declining new student enrollment, which require more effective marketing strategies. A quantitative survey method was employed with 326 respondents from 60 high schools, vocational schools, and community learning centers in Bandung and the surrounding areas. Multiple linear regression analysis was conducted on 241 respondents in grades 10–12 who were aware of University X, with the results compared to those of 145 respondents from grades 11–12. In the overall analysis, price and people significantly influence purchase intention, while promotion shows a very weak effect. Product, place, and physical evidence show no significant effect. In the grade 11–12 segment, process is the only significant variable. The findings recommend marketing strategies focused on improving pricing and scholarship schemes, enhancing human resource competencies among lecturers, academic staff, students, and alumni, strengthening promotional efforts, and optimizing service processes. The study confirms that, in the higher education context, price, people, and process are dominant predictors of purchase intention, providing strategic insights for University X decision-makers.